Perspectives on Fully Synthesized Sustainable Aviation Fuels: Direction and Opportunities - Kramer, Stephen; Andac, Gurhan; Heyne, Joshua; Ellsworth, Joseph; Herzig, Peter; Lewis, Kristin C. (Frontiers in Energy Research, 2022)
The aviation sector seeks to reduce greenhouse gas (GHG) emissions, with manufacturers and airlines announcing “zero-emission” goals and plans. Reduced carbon aviation fuels are central to meeting these goals. However, current and near-term aircraft, which will remain flying for decades, are designed around the combustion of petroleum-based aviation kerosene (e.g., Jet A/A-1). Therefore, the industry has focused on the qualification and approval of synthesized (e.g., non-petroleum-based) aviation fuel components with maximum blend limit percentages to avoid the blended fuel having properties outside the accepted ranges for Jet A/A-1. The synthesized components approved for blending are not necessarily interchangeable with Jet A/A-1. They may lack certain required chemical components, such as aromatics, or may have other characteristics outside the allowable ranges. To ensure safety, these synthesized aviation fuel components are only qualified to be used in commercial aviation when blended up to approved limits. The sector seeks to move toward the capability of using 100% synthesized aviation fuels that also meet sustainability criteria, known as sustainable aviation fuels, or SAF. However, these fuels must be developed, assessed, and deployed appropriately. This paper explores key questions relating to the introduction of 100% SAF, concluding that: • Near-term unblended synthesized aviation fuels must be “drop-in,” meaning they are compatible with existing aircraft and infrastructure. • Stand-alone complete fuels could be qualified within 1–2 years, with blends of blending components to reach 100% synthesized fuels to follow. • Sustainability criteria, while critical to sector acceptance, will continue to be assessed separately from technical performance.